630.COMPARATIVE ANALYSIS OF WESTERN BALKAN FOR GRANTING STATE AID FOR 2017 WITH RESPECT TO ENVIRONMENTAL SUPPORT: CASE OF SERBIA, ALBANIA AND MACEDONIA - Vladimir, Naumovski; Filip, Ivanovski; Zoran, Sapuric; Dame Dimitrovski (MECHANICAL ENGINEERING – SCIENTIFIC JOURNAL, 2021)
The purpose of the comparative analysis is to present the whole overview of the granting state aid in Serbia, Albania and Macedonia for 2017, based on the data obtained by the annual reports published by the authorities responsible for the area of state aid in the countries named above. The analysis consists of processing such data published in the annual reports of the countries named above, focused the overview of the total state aid granted for 2017 in the countries as well as in what form and for what purpose such aid is granted by the state aid providers. The attempt with this analysis is to process the data through a spreadsheet overview, taking into account different parameters, it is for the purpose to show the focus of each country whose economic sectors were targeted of its support, but also to have an overview of what kind of state aid it is and for what purpose it is granted by the state aid providers in the countries named above. Especial overview is done to realize the amount of state aid granted for projects or activities in the filed of protection of environment. Processing the data of the annual reports, but also through more detailed analysis of the content of such reports, the intention is to find elements that make up what is common and different in terms of how such annual reports are compiled (prepared) by the competent authorities from the countries named above.